THE BORDERS OF CULTURAL PLURALITIES: CONSTRUCTION AND POLITICAL REALITY - I. V. Gibelev (Концепт: философия, религия, культура, 2017)
The article explores the issue of cultural pluralities’ borders transformation in the contemporary world. Political borders are considered a type of cultural sets’ boundaries that were opened up by the European project of universal culture. Transcendental ideas played a pivotal role in constructing universalism. Through the decay of transcendent dimension in cross-border interaction studies, the concept of space attracted considerable attention. The spatial schemes of environmental perception dominated in Western thought for two and a half thousand years. G.W.F. Hegel summed up the characteristics of modern European mind: “The truth of space is time”. Spatial logic expresses the essence of time. According to Hegel, at the beginning of the 19th century the World Spirit came to its total selfidentity, thus time flow lost all sense, the end of history happened. Of course, it does not mean that the element of time became extinct and historical process as a succession of events came to an end. The “end of history” thesis reflects certain embodiment of Enlightenment ideals in social and cultural practices. However, the end of history based on temporal self-identification consciousness, opened up a new horizon of human history - its existence in a net of spatial (cultural) pluralities. Cultural sets exist as mutually intersecting, and its external border in a global world turns out to be a closed limit. In 1990s the conception of the “borderless world” was developed proclaiming that boundaries’ disappearance was natural and calling to destroy the borders. Nowadays, we are witnessing boundaries’ simultaneous destruction and strengthening process. The paper asserts that scanty knowledge of ontological sense of a boundary in humanitarian studies and practices is caused by an excessive attention to constructing abilities of human mind. Boundary phenomenon comprehension presupposes raising the question of possible forms of transcendence presence in contemporary non-transcendent world.